EMERGENCE AND INCREASE OF PROBLEM LOANS IN BANKS (British Journal of Global Ecology and Sustainable Development, 2024)
This scientific article examines the responsibility, established and other management mechanisms for the emergence and growth of problem loans in banks. Problem loans are loans granted to the property of banks, which are difficult for borrowers to fulfill the terms and conditions set by the bank. This dissertation discusses the main causes of problem loans, their correction, methods and strategies of banks in their management. The increase in the weight of problem loans threatens the state-owned enterprise sector, negatively affects the activities of banks and completely hinders the development of production. Therefore, it is necessary for banks and regulators to develop more effective management strategies for problem loans.